PEER-LED AND TEACHER-LED GUIDED INQUIRY TEACHING APPROACHES ON STUDENTS’ ACADEMIC PERFORMANCE IN CHEMISTRY (UNIZIK Journal of STM Education, 2024)
The study was carried out to examine the effect of peer-led and teacher-led guided inquiry teaching approaches on students’ academic performance in Chemistry in Uyo Local Government Area. Three research questions and three hypotheses were formulated to guide the study. The design for the study was a quasi-experimental pretest-posttest design. The population for the study consisted of all the 2625 senior secondary two chemistry students in fifteen (15) public co-educational secondary schools in Uyo Local Government Area. A sample size of 97 SS 2 Chemistry students was used for the study. A simple random sampling technique was used in selecting two public co-educational secondary schools in the study area. In each selected school, one intact class of SS 2 Chemistry students was used for the study. The instrument used for data collection was the Chemistry Performance Test on Stoichiometry (CPTS). Two measurement and evaluation experts and a chemistry education lecturer subjected the instrument to face and content validation. A reliability coefficient of 0.85 was obtained using Kuder-Richardson formula-20 (KR-20). Mean and standard deviation were used to answer the research questions while Analysis of Covariance was used to test the hypotheses at a 0.05 level of significance. The findings showed that students taught the concept of stoichiometry using a peer-led guided inquiry teaching approach performed better than students taught using a teacher-led guided inquiry teaching approach. The finding also showed no significant difference in the mean performance scores between male and female students taught the concept of stoichiometry using peerled and teacher-led guided inquiry approaches. Based on the study's findings, it was concluded that the peer-led guided inquiry approach enhanced students’ academic performance in Chemistry than the teacher-led guided inquiry approach in Uyo Local Government Area. It is recommended among others that a peer-led guided inquiry approach should be adopted by Chemistry teachers in the teaching and learning of stoichiometry and other Chemistry concepts.
Keywords: Peer-led guided inquiry, teacher-led guided inquiry, stoichiometry, academic performance and gender.